The Detection of Physiological Changes Using a Triaxial Accelerometer and Temperature Sensor-Equipped Bolus-Type Biosensor in Calves - Leegon Hong; Younghye Ro; Atsushi Kimura; Woojae Choi; Danil Kim (Animals)
In this study, a newly developed small wireless bolus biosensor, equipped with a triaxial accelerometer and temperature sensors, was applied to assess physiological changes in calves. The biosensor was orally implanted in calves, and its retention rate and location in the forestomach were examined. Data transmitted at 10 min intervals were analyzed to determine the characteristics of the calves at 10 and 100 days of age. Additionally, the daily averages of the vector magnitude (DV), changes in V over time (DV1), and reticular temperature (DRT) were analyzed during the experimental period. The biosensor was orally administered to twelve calves (six beef and six dairy) within 22 days of birth. Except for two regurgitated devices, the sensors transmitted data normally in a wireless manner for 15 weeks, recording physiological changes in the calves. The location of the biosensors was confirmed to be the reticulum. The analysis revealed that the V and V1 values were influenced by the physical characteristics of the biosensor’s location. During weaning, DV and DV1 values first increased and then decreased compared to pre-weaning, while the DRT increased post-weaning and remained elevated. These findings suggest that these types of biosensors can be used for monitoring calf health; however, further research is needed to determine their ability to detect pathological states.